Oral vaccination as a potential strategy to manage chronic wasting disease in wild cervid populations - Napper, Scott; Schatzl, Hermann M. (Frontiers in Immunology, 2023)
Prion diseases are a novel class of infectious disease based in the misfolding of the cellular prion protein (PrPC) into a pathological, self-propagating isoform (PrPSc). These fatal, untreatable neurodegenerative disorders affect a variety of species causing scrapie in sheep and goats, bovine spongiform encephalopathy (BSE) in cattle, chronic wasting disease (CWD) in cervids, and Creutzfeldt-Jacob disease (CJD) in humans. Of the animal prion diseases, CWD is currently regarded as the most significant threat due its ongoing geographical spread, environmental persistence, uptake into plants, unpredictable evolution, and emerging evidence of zoonotic potential. The extensive efforts to manage CWD have been largely ineffective, highlighting the need for new disease management tools, including vaccines. Development of an effective CWD vaccine is challenged by the unique biology of these diseases, including the necessity, and associated dangers, of overcoming immune tolerance, as well the logistical challenges of vaccinating wild animals. Despite these obstacles, there has been encouraging progress towards the identification of safe, protective antigens as well as effective strategies of formulation and delivery that would enable oral delivery to wild cervids. In this review we highlight recent strategies for antigen selection and optimization, as well as considerations of various platforms for oral delivery, that will enable researchers to accelerate the rate at which candidate CWD vaccines are developed and evaluated.